Predicting brain tumor regrowth in relation to motor areas by functional brain mapping. Issue 2 (6th September 2017) - Sollmann, Nico; Laub, Tobias; Kelm, Anna; Albers, Lucia; Kirschke, Jan S; Combs, Stephanie E; Meyer, Bernhard; Krieg, Sandro M
Abstract: Background: Due to frequent recurrences, high-grade gliomas still confer a poor prognosis. Several regrowth prediction models have been developed, but most of these models are based on cellular models or dynamic mathematical calculations, thus limiting direct clinical use. The present study aims to evaluate whether navigated transcranial magnetic stimulation (nTMS) or functional magnetic resonance imaging (fMRI) may be used to predict the direction of tumor regrowth. Methods: Sixty consecutive patients with high-grade gliomas were enrolled prospectively and analyzed in a case-control design after tumor recurrence. All patients underwent serial MRI after surgery and suffered from recurrent tumors during a mean follow-up of 13.2 ± 14.9 months. Tumor regrowth speed and direction were measured in relation to motor areas defined by nTMS, nTMS-based tractography, and fMRI. Depending on initial resection, patients were separated into three groups (group 1: without residual tumor, group 2: residual tumor away from motor areas, and group 3: residual tumor facing motor areas). Results: Sixty-nine percent of patients in group 1, 64.3% in group 2, and 66.7% in group 3 showed tumor recurrence towards motor eloquence on contrast-enhanced T1-weighted sequences ( P = .9527). Average growth towards motor areas on contrast-enhanced T1-weighted sequences was 0.6 ± 1.5 (group 1), 0.6 ± 2.4 (group 2), and 2.3 ± 5.5 (group 3) mm/month ( P = .0492). Conclusion: This study suggests a new strategy to predict tumor regrowth patterns in high-grade glioma patients. Our approach could be directly applied in the clinical setting, thus having clinical impact on both surgical treatment and radiotherapy planning. Ethics Committee Registration Number: 2793/10.